DAMNATIO MEMORIAE: MEMORY AND IDENTITY OF THE (POST)COMMUNIST CROATIA - Karla Lebhaft (University of Bucharest Review. Literary and Cultural Studies Series, 2022)
In its post-war positioning in relation to the Western-European space and the Soviet Union in the aftermath of the famous 1948 split, Yugoslavia showed a tendency towards forming a unique, but rather hybrid federative identity. Cultural politics was used as an instrument in breaking from the Soviet prototype model and in adapting to Western values, as manifested in Yugoslavian ethics and aesthetics. In line with tendencies in the West for abstract forms in visual arts, Yugoslavia adopted and applied them in public memorial sculpture. Such monuments represent a unique phenomenon that requires consideration within the context of the so-called “socialist modernism”. Consequently, one of the postulates of this research is that the aesthetic category is indeed one of the crucial elements in constituting the Yugoslav identity. Within that framework, I will analyze the notion of 'trauma' as: 1) the place of a previous trauma which is positively commemorated by a certain monumental corpus; 2) subsequently inscribed onto the same memorial place amidst the shifts of political systems. The radical shifts in political structures in the 1990s, the demise of the federative regime, as well as the significant number of social norms and convention, were accompanied by the systematic elimination and devastation of formerly communist abstract monuments which were now seen as material reminders of oppression. Destruction thus became ritualistic cleansing, meant to legitimize the newly liberated national entities. Therefore, the replacing of the places of remembrance with the places of forgetting is to be equated with a removal of the symbols of what was seen as the interrupted continuity of a nation.